Natural Radioactivity In Domestic Water Sources In Northern Peninsular Malaysia - Muhammad, Bashir Gide (2012)

(untitled)
Bioaccumulation of dissolved radioactive materials through drinking water is considered an important pathway for long-term health concerns. Thus, the World Health Organization (WHO) guidelines for drinking water radiological quality were adopted to screen the adequately utilized surface water resources in northern peninsular Malaysia for natural radioactivity. The sampling locations were 12, 26, 16 and 19 from the states of Penang, Perlis, Kedah and Perak, respectively. Firstly, gross alpha and gross beta activity concentrations were measured in the raw and subsequently the treated domestic water supply sources using International Standard Organisation (ISO) proceedures.